Is Government a Good Investment? Public Transfers for Filipino Generations Born in 1950 to 2020 - Michael Ralph M. Abrigo; Katha Ma-i Estopace; Zhandra C. Tam; Kean Norbie F. Alicante (Philippine Institute for Development Studies (PIDS), 2022)
We present a new comprehensive and consistent set of public transfer accounts disaggregated by age and by major government programs that spans from 1950 to 2020. Based on these public transfer accounts, we find that except for some programs, particularly social health insurance and old-age pensions, the Philippines' public transfer system as a whole is fiscally sustainable with cumulative lifetime net contributions due to government across cohorts. The implied rates of return from key social protection programs also approximate market interest rates, especially when these programs are taken together, which suggests that the country's public transfer system closely mimics competitive market outcomes.
Keywords: 330; public sector; demographic change; National Transfer Account; intergenerational transfers; intergenerational equity; fiscal sustainability